Financial Development and Economic Growth Nexus - Tandan, Laxman; Khanal, Khagashyor; Kafle, Ananta Raj (KIC International Journal of Social Science and Management, 2022)
This paper attempts to examine the Nexus between finance growth by indigenised economic growth, financial development, fixed gross capital, foreign direct investment, total trade, population and remittance for Nepal during the period from 1981-2021. Using ARDL, there exists evidence of co-integration among the variables used in the model, based on ARDL model and causality test, suggests that there is long run relationship and long run adjustment in short run. Furthermore, the result also point out that fixed gross capital and total trade on not contributed to achieve economic growth in the Nepalese context. Both the sustainability diagnostic and residual diagnosis test indicates that the estimation is free from spurious form.